2007
DOI: 10.1021/je700182n
|View full text |Cite
|
Sign up to set email alerts
|

Perfluorinated n-Alkanes CmF2m+2 (m < 7):  Second pVT-Virial Coefficients, Viscosities, and Diffusion Coefficients Calculated by Means of an (n-6) Lennard-Jones Temperature-Dependent Potential

Abstract: The perfluorinated n-alkanes C m F2 m +2 (m = 1 to 6) are widely used and expensive substances that are not only of technological interest for the semiconductor industry but also powerful greenhouse gases having an important impact on the atmosphere. This paper presents tables with recommended thermophysical data in the temperature range (200 to 1000) K at pressures of ≤0.1 MPa. Second pVT-virial coefficients B, viscosities η, and diffusion coefficients D are calculated by means of an (n-6) Lennard-Jones tem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 34 publications
1
5
0
Order By: Relevance
“…As was observed earlier for the alkanes C m H 2 m +2 , and perfluoroalkanes C m F 2 m +2 R m ( T = 0 K) and ε( T = 0 K) of the alkenes and cyclopropane increase with increasing size of the molecules. Also comparable to our findings for C m H 2 m +2 and C m F 2 m +2 , the repulsive parameter n does not follow a simple trend and varies between 17.1 (propene) and 38.3 (iso-butene).…”
Section: Resultssupporting
confidence: 79%
See 2 more Smart Citations
“…As was observed earlier for the alkanes C m H 2 m +2 , and perfluoroalkanes C m F 2 m +2 R m ( T = 0 K) and ε( T = 0 K) of the alkenes and cyclopropane increase with increasing size of the molecules. Also comparable to our findings for C m H 2 m +2 and C m F 2 m +2 , the repulsive parameter n does not follow a simple trend and varies between 17.1 (propene) and 38.3 (iso-butene).…”
Section: Resultssupporting
confidence: 79%
“…The LJTDP has been successfully applied before to a number of pure gases like the alkanes 31,32 and perfluoroalkanes. 33 We have shown that it performs also very well in the prediction of B, η, and D of binary mixtures of alkanes and other gases. 34,35 To give a comprehensive overview on the molecules with sum formula C m H 2m , we not only consider the alkenes but also try to include the two cyclic compounds cyclopropane (C 3 H 6 ) and cyclobutane (C 4 H 8 ) in our studies.…”
Section: Introductionmentioning
confidence: 73%
See 1 more Smart Citation
“…It is accepted that octafluoropropane is completely stable and entirely nontoxic. 6 Only a few liquid phase density measurements for PFC-218 are reported in the open literature. Table 1 gives an overview of the literature sources for experimental p−ρ−T data for octafluoropropane together with the corresponding temperature and pressure region, and the number of data points.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Among them, octafluoropropane (C 3 F 8 , PFC-218 in ANSI/ASHRAE nomenclature) is widely used in the most varied industrial applications, in particular under the name R-218 as a component of mixture refrigerants. It is accepted that octafluoropropane is completely stable and entirely nontoxic …”
Section: Introductionmentioning
confidence: 99%